Subjective sleep quality and electronic cigarette dependence, perceived risks of use, and perceptions about quitting electronic cigarettes. (March 2020) - Zvolensky, Michael J.; D'Souza, Johann; Garey, Lorra; Alfano, Candice A.; Mayorga, Nubia A.; Peraza, Natalia; Gallagher, Matthew W.
Highlights: Sleep quality was examined among e-cigarette users in relation to e-cigarette processes. Poor sleep quality was associated with greater electronic cigarette dependence. Poor sleep quality was related to more perceived barriers to quitting e-cigarettes. Sleep quality was not associated with perceived risks of electronic cigarette use. Abstract: Introduction: Although subjective sleep quality has been associated with combustible cigarette use, little is known about its role in electronic cigarette (e-cigarette) use or beliefs about use. To address this gap, the current study examined subjective sleep quality among adult e-cigarette users in relation to e-cigarette dependence, perceived risks of e-cigarette use, and perceived barriers for quitting e-cigarettes. Methods: A cross-section design was employed. Participants included 304 e-cigarette users (53.6% female, Mage  = 36.7 years,   SD  = 10.3, 75% were combustible cigarette users) using a Qualtrics platform. Results: Results indicated that poorer subjective sleep quality was significantly related to greater e-cigarette dependence and perceived barriers for quitting e-cigarettes (Δ R 2  = 0.06, p  < .001 for each model) but was not significantly associated with perceived risks of e-cigarette use. Conclusions: This work provides novel evidence for the potential role of subjective sleep quality in e-cigarette dependence and beliefs about quitting. To the extent sleep quality is related to e-cigarette addiction and cognition, it represents an important construct to assess and target for change in efforts to facilitate change in e-cigarette dependence and perceived barriers for quitting. Implications: This study is among the first data to link subjective sleep quality to e-cigarette dependence and beliefs about risk of use and perceptions about barriers for quitting among adults. Similar to results found for combustible cigarettes, these findings suggest that subjective sleep quality may be important to consider in efforts to facilitate change in e-cigarette dependence and perceived barriers for quitting.